Outcomes Following Surgical Repair of Sinus Venosus Atrial Septal Defects: A Systematic Review and Meta‐Analysis - Ryaan El‐Andari; Muhammad Moolla; Kevin John; Ashley Slingerland; Sandra Campbell; Jeevan Nagendran; Yongzhe Hong; Anoop Mathew (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background Sinus venosus atrial septal defect (SVASD) is a rare congenital cardiac anomaly comprising 5% to 10% of all atrial septal defects. Although surgical closure is the standard treatment for SVASD, data on outcomes have been confined to small cohorts. Thus, we conducted a systematic review of the outcomes of SVASD repair. Methods and Results The primary outcome was death. Secondary outcomes encompassed atrial fibrillation, sinus node dysfunction, pacemaker insertion, cerebrovascular accident, reoperation, residual septal defect, superior vena cava obstruction, and reimplanted pulmonary vein obstruction. Pooled incidences of outcomes were calculated using a random‐effects model. Forty studies involving 1320 patients who underwent SVASD repair were included. The majority were male patients (55.4%), with 88.0% presenting with associated anomalous pulmonary venous connection. The weighted mean age was 18.6±12.5 years, and the overall weighted mean follow‐up period was 8.6±10.4 years. The in‐hospital mortality rate was 0.24%, with a 30‐day mortality rate of 0.5% reported in 780 patients. Incidences of atrial fibrillation, sinus node dysfunction, pacemaker insertion, and cerebrovascular accident over the long‐term follow‐up were 3.3% (2.18%–4.93%), 6.5% (5.09%–8.2%), 2.23% (1.34%–3.57%), and 2.03% (0.89%–2.46%) respectively. Reoperation occurred in 1.36% (0.68%–2.42%) of surgeries, residual septal defect in 1.34% (0.69%–2.42%), superior vena cava obstruction in 1.76% (1.02%–2.9%), and reimplanted pulmonary vein obstruction in 1.4% (0.7%–2.49%). Conclusions This is the first comprehensive analysis of outcomes following surgical repair of SVASD. The findings affirm the safety and effectiveness of surgery, establishing a reference point for evaluating emerging transcatheter therapies. Safety and efficacy profiles comparable to surgical repair are essential for widespread adoption of transcatheter treatments.